Cytokines as Targets of Novel Therapies for Graves’ Ophthalmopathy - Fallahi, Poupak; Ferrari, Silvia Martina; Elia, Giusy; Ragusa, Francesca; Paparo, Sabrina Rosaria; Patrizio, Armando; Camastra, Stefania; Miccoli, Mario; Cavallini, Gabriella; Benvenga, Salvatore; Antonelli, Alessandro (Frontiers in Endocrinology, 2021)
Graves' disease (GD) is an organ-specific autoimmune disorder of the thyroid, which is characterised by circulating TSH-receptor (TSH-R) stimulating antibodies (TSAb), leading to hyperthyroidism. Graves’ ophthalmopathy (GO) is one of GD extra-thyroidal manifestations associated with the presence of TSAb, and insulin-like growth factor-1 receptor (IGF-1R) autoantibodies, that interact with orbital fibroblasts. Cytokines are elevated in autoimmune (i.e. IL-18, IL-6) and non-autoimmune hyperthyroidism (i.e. TNF-, IL-8, IL-6), and this could be associated with the chronic effects of thyroid hormone increase. A prevalent Th1-immune response (not related to the hyperthyroidism per se, but to the autoimmune process) is reported in the immune-pathogenesis of GD and GO; Th1-chemokines (CXCL9, CXCL10, CXCL11) and the (C-X-C)R3 receptor are crucial in this process. In patients with active GO, corticosteroids, or intravenous immunoglobulins, decrease inflammation and orbital congestion, and are considered first-line therapies. The more deepened understanding of GO pathophysiology has led to different immune-modulant treatments. Cytokines, TSH-R and IGF-1R (on the surface of B and T lymphocytes, and fibroblasts), and chemokines implicated in the autoimmune process, are possible targets of novel therapies. Drugs that target cytokines (etanercept, tocilizumab, infliximab, adalimumab) have been tested in GO, with encouraging results. The chimeric monoclonal antibody directed against CD20, RTX, reduces B lymphocytes, cytokines and the released autoantibodies. A multicenter, randomized, placebo-controlled, double-masked trial has investigated the human monoclonal blocking antibody directed against IGF-1R, teprotumumab, reporting its effectiveness in GO. In conclusion, large, controlled and randomized studies are needed to evaluate new possible targeted therapies for GO.